PERBANDINGAN EFEK POVIDONE IODINE DENGAN SARI KURMA TERHADAP PENYEMBUHAN LUKA SAYAT PADA MENCIT (MUS MUSCULUS) - DINDA NAWA MIFTAH SEMBIRING; ERY SUHAYMI (LP2MTBM MAKARIOZ, 2020)
When a wound occurs, human body has its own mechanisms to restore the injured tissue by forming the new functionaltissues. Broadly the first treatment of wounds that are often used by the public is antiseptic. Antiseptics are substances thatare used to inhibit growth or kill microorganisms that live on the surface of the body. The most commonly used antiseptic ispovidone iodine which is a chemical complex of polyvinyl pyrrolidone and iodine elements. But povidone still has some sideeffects in its use.Dates (Phoenix Dactylifera) is a fruit that is very familiar with people lives, especially for muslims. Datescontain antioxidant compounds namely phenolic compounds such as flavonoids. Flavonoids are hydroxylated phenolicsubstances and known to be synthesized by plants in response to microbainfection. Therefore dates and processed productscan be used as natural antiseptics. To compare the effectiveness of wound care using palm juice against wound healingcompared to povidone iodine in mice in improving the wound recovery process. This study uses an experimental method thatis designing a post test with a design control group to compare wound utilization using palm juice and povidone iodine to thetreatment of incision in mice. The average speed of wound healing, palm juice had the fastest time of 6.56 days followed bypovidone iodine 10.56 days, while controls were 11.67 days. Palm juice are more effective in wound healing compared topovidone iodine.